Наукометрический анализ состояния и тенденций развития научной проблемы: нa примере материалов по биосенсорам - Танатар, Н.В. (Биополимеры и клетка, 1990)
В результате структурного анализа проблемы построен классификатор, с помощью котрого содержание рефератов массива информации было переведено в набор чисел (индексы). Затем осуществлена математическая обработка формально описанного массива информации и последующая экспертная оценка полученных данных. У результаті структурного аналізу проблеми побудовано класифікатор, за допомогою якого зміст рефератів масиву інформації було переведено в набір чисел (індекси). Надалі здійснено математичну обробку формально описаного масиву інформації і подальшу експертну оцінку отриманих даних. The analysis of information file formed on the abstract journals was used to assess the state and trends of the development of biosensor studies. The biosensor problem has determined three integrated parameters subsequently referred to as: the substance under study, bioreceptor and sensor. The classifier based on this structure has allowed performing a fonnalistic description of the subject-matter of publications and made it possible to form the publication matrices. The subsequent mathematical data processing has shown that just now there are 35 main trends for further research. Following groups for their formalistic classification are possible: the casual trends, the trends to be completed, the developing ones, the intensively developing trends and new ones.